Game theory using by of weights Finding values (Journal of the College of Basic Education, 2022)
In this paper we introduce weighting method where this method is used for solving multi-objective linear programming Problem, such that this method transform the multi – objectives problem into single –objective programming form . Also new proposition is constructed for solving multi-objective functions, where this proposition dependent on weighting method and Game theory